Pengaruh Media Mind Mapping dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Sejarah Kebudayaan Islam di MAN 2 Kota Bogor - Novia Alfany; Fahmi Irfani; Rahmatul Husni (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Education is a fundamental aspect of students' character formation and intelligence. One of the subjects that plays an important role in shaping historical understanding and Islamic values is the subject of SKI. However, in practice, history learning often faces various obstacles, both in terms of learning methods, student involvement and material understanding. This research aims to find out the influence of Mind Mapping media in improving students' learning outcomes in Islamic cultural history subjects at MAN 2 Bogor City. The method used in this study was quantitative by using an experimental approach with the design of the Quasi Experimental Design (Experimental All) using the Pre-Test Post-Test Non-Equivalent Control Design Group consisting of a control group and an experimental group treated differently. Research results: 1) using Mind Mapping media has a significant effect in improving student learning outcomes on the material of the History of Islamic Kingdoms in Java at MAN 2 Bogor City. This is indicated by the results of the t-test with a significance result of 0.011. 2) The effectiveness of Mind Mapping media is proven by the results of the N-Gain increase obtained in the control class by the less effective category. While in the control class it is quite effective.